The Sinorhizobium meliloti fur Gene Regulates, with Dependence on Mn(II), Transcription of the sitABCD Operon, Encoding a Metal-Type Transporter - Chao, Tzu-Chiao (American Society for Microbiology, 2004)
Sinorhizobium meliloti is an alpha-proteobacterium able to induce nitrogen-fixing nodules on roots of specific legumes. In order to propagate in the soil and for successful symbiotic interaction the bacterium needs to sequester metals like iron and manganese from its environment. The metal uptake has to be in turn tightly regulated to avoid toxic effects. In this report we describe the characterization of a chromosomal region of S. meliloti encoding the sitABCD operon and the putative regulatory fur gene. It is generally assumed that the sitABCD operon encodes a metal-type transporter and that the fur gene is involved in iron ion uptake regulation. A constructed S. meliloti sitA deletion mutant was found to be growth dependent on Mn(II) and to a lesser degree on Fe(II). The sitA promoter was strongly repressed by Mn(II), with dependence on Fur, and moderately by Fe(II). Applying a genome-wide S. meliloti microarray it was shown that in the fur deletion mutant 23 genes were up-regulated and 10 genes were down-regulated when compared to the wild-type strain. Among the up-regulated genes only the sitABCD operon could be associated with metal uptake. On the other hand, the complete rhbABCDEF operon, which is involved in siderophore synthesis, was identified among the down-regulated genes. Thus, in S. meliloti Fur is not a global repressor of iron uptake. Under symbiotic conditions the sitA promoter was strongly expressed and the S. meliloti sitA mutant exhibited an attenuated nitrogen fixation activity resulting in a decreased fresh weight of the host plant Medicago sativa.